Paladin is a phosphoinositide phosphatase regulating endosomal VEGFR2 signalling and angiogenesis. (28th December 2020) - Nitzsche, Anja; Pietilä, Riikka; Love, Dominic T; Testini, Chiara; Ninchoji, Takeshi; Smith, Ross O; Ekvärn, Elisabet; Larsson, Jimmy; Roche, Francis P; Egaña, Isabel; Jauhiainen, Suvi; Berger, Philipp; et al.
Abstract: Cell signalling governs cellular behaviour and is therefore subject to tight spatiotemporal regulation. Signalling output is modulated by specialized cell membranes and vesicles which contain unique combinations of lipids and proteins. The phosphatidylinositol 4, 5‐bisphosphate (PI(4, 5)P2 ), an important component of the plasma membrane as well as other subcellular membranes, is involved in multiple processes, including signalling. However, which enzymes control the turnover of non‐plasma membrane PI(4, 5)P2, and their impact on cell signalling and function at the organismal level are unknown. Here, we identify Paladin as a vascular PI(4, 5)P2 phosphatase regulating VEGFR2 endosomal signalling and angiogenesis. Paladin is localized to endosomal and Golgi compartments and interacts with vascular endothelial growth factor receptor 2 (VEGFR2) in vitro and in vivo . Loss of Paladin results in increased internalization of VEGFR2, over‐activation of extracellular regulated kinase 1/2, and hypersprouting of endothelial cells in the developing retina of mice. These findings suggest that inhibition of Paladin, or other endosomal PI(4, 5)P2 phosphatases, could be exploited to modulate VEGFR2 signalling and angiogenesis, when direct and full inhibition of the receptor is undesirable. SYNOPSIS: This study identifies Paladin as a vascular PI(4, 5)P2 phosphatase, which restricts VEGFR2 internalization and activation of downstream signaling, thereby dampening angiogenesis. Paladin is a phosphoinositide phosphatase with preference for PI(4, 5)P2. VEGF‐A induces co‐localization of Paladin with VEGFR2 in EEA1 + early endosomes. Paladin deficiency promotes increased VEGFR2 phosphorylation, internalization, and ERK1/2 signalling. Increased ERK1/2 signalling in Paladin knockout mice leads to endothelial cell hypersprouting in physiological and pathological retinal angiogenesis. Abstract : This study identifies Paladin as a vascular PI(4, 5)P2 phosphatase, which restricts VEGFR2 internalization and activation of downstream signaling, thereby dampening angiogenesis.